Environmental monitoring of soil pollution in urban areas (a case study from Heraklion city, Central Crete, Greece) - Kokinou, E.; Belonaki, C.; Sakadakis, D.; Sakadaki, K. (Bulletin of the Geological Society of Greece, 2013)
Main scope of the present study is to combine topographic and geological data, magnetic susceptibility and thermomagnetic analysis in order to investigate the magnetic properties of the near surface soils in possible polluted urban areas. For this purpose, a power plant with a dense traffic net around it, located in the NW section of Heraklion city in Crete was selected to be the study area. Surface soil samples have been collected from the area under investigation and they were analyzed in order to estimate the spatial distribution of the magnetic susceptibility. Loci of high values of the magnetic susceptibility within the study area gave rise to further proceed to thermomagnetic analysis of the selected samples. GIS techniques were used for mapping the magnetic measurements on the various topographic and geological features of the area. The digital elevation model was created by the digitization of the topographic map contours (1:5000 scale maps). The combination of the above techniques indicate high values of the magnetic susceptibility especially in the northeastern part of the investigated area, possibly related to pollution due to the presence of heavy metals.